The Optimization of Leading Sectors in Alleviating Poverty and Inequality in the Special Region of Yogyakarta Province - Muhammad Viktar Sabilillah Tafarel; Ira Rahayuningtyas (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
This study aims to identify and analyze the leading economic sectors in the Special Region of Yogyakarta with the goal of reducing high levels of poverty and inequality compared to other provinces in Indonesia. The methods employed include Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis, and Klassen Typology, using ADHK GDP data from 2018 to 2022 across 61 sectors and sub-sectors. The analysis revealed varying results: LQ and DLQ identified 8 leading sectors; Shift-Share Analysis identified 6; and Klassen Typology identified 15. The intersecting sectors revealed that there were only three leading economic sectors including: the horticultural subsector, the information and communication sector, and other service sectors. Policy implications suggest utilizing Sultan Ground and BUMKal for horticultural production, enhancing financial literacy within the information and communication sector, and promoting locally-based sustainable tourism in other service sectors to drive equitable and sustainable regional development.